River rhythmicity: A conceptual means of understanding and leveraging the relational values of rivers. Issue 4 (13th May 2022) - Jackson, Sue; Anderson, Elizabeth P.; Piland, Natalia C.; Carriere, Solomon; Java, Lilia; Jardine, Timothy D.
Abstract: River rhythmicity refers to the periodic, recurrent phenomena of a riverscape that are synchronized with the rise and fall of river water, creating regimes of river time. River rhythmicity can serve as a lens into the temporal dimension of river formation and socio‐ecological dynamics that are of great interest to many disciplines. In this paper, we introduce river rhythmicity as a conceptual and analytical framework to unify riparian human communities, academic disciplines and water agencies in approaching research and management of rivers. We also explore how the disruptions to riverine rhythms that are experienced by river‐dwelling communities, and are often visible in river discharge data through time, reconfigure, hinder or sever relationships between people and rivers. To ground our discussion in practical, lived experience, we provide brief descriptions of regimes of river time to demonstrate how rhythmic patterns established with rivers in north‐central Canada and Amazonian Colombia shape the lives of two of our co‐authors. By prioritizing holistic accounts of river rhythms, we can elucidate a fuller range of phenomena and their dynamic interactions, revealing riverscape features that are highly valued by local communities yet not often visible to any one discipline. Rhythmicity provides a conceptual framework to help address several challenges facing river conservation and water allocation dilemmas. By emphasizing relationality, it serves to (a) move beyond a biophysical framing of human‐nature connectedness by demonstrating that dynamic processes and relationships are constitutive of rivers, not derivative of them; (b) enhance understanding of how the temporal dimensions of riverine relationships and river dwelling are experienced; (c) highlight the socio‐cultural consequences of changes to river time and (d) centre socially embedded relationships with rivers forged from generations of observations of care and reciprocity. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: La ritmicidad del río se refiere a los fenómenos periódicos y recurrentes de un paisaje fluvial que se sincronizan con el ascenso y descenso del agua del río, creando regímenes de tiempo de los ríos. La ritmicidad del río puede servir como lente de la dimensión temporal de la formación del río y la dinámica socio‐ecológica que son de gran interés para muchas disciplinas. En este artículo, presentamos la ritmicidad de los ríos como un marco conceptual y analítico para unificar las comunidades humanas ribereñas, las disciplinas académicas y las agencias de agua al abordar la investigación y la gestión de los ríos. También exploramos cómo las interrupciones en los ritmos fluviales que experimentan las comunidades que habitan en los ríos, y que a menudo son visibles en los datos de descarga del río a lo largo del tiempo, reconfiguran, dificultan o rompen las relaciones entre las personas y los ríos. Para basar nuestra discusión en una experiencia práctica y vivida, proporcionamos breves descripciones de los regímenes del tiempo de los ríos para demostrar cómo los patrones rítmicos establecidos con los ríos en el centro‐norte de Canadá y la Amazonía de Colombia dan forma a las vidas de dos de nuestros coautores. Al priorizar los relatos holísticos de los ritmos de los ríos, podemos dilucidar una gama más completa de fenómenos y sus interacciones dinámicas, revelando características del paisaje fluvial que son muy valoradas por las comunidades locales pero que a menudo no son visibles para ninguna disciplina. La ritmicidad proporciona un marco conceptual para ayudar a abordar varios desafíos que enfrentan los dilemas de conservación de ríos y asignación de agua. Enfatizar en la relacionalidad sirve para (i) ir más allá del encuadre biofísico de la conectividad humanos‐naturaleza demostrando que los procesos y relaciones dinámicos son constitutivos de los ríos, no derivados de ellos; (ii) mejorar la comprensión de cómo se experimentan las dimensiones temporales de las relaciones y las viviendas fluviales; (iii) destacar las consecuencias socioculturales de los cambios en el tiempo de los ríos, y (iv) centrar las relaciones socialmente arraigadas con los ríos forjadas a partir de generaciones de observaciones de cuidado y reciprocidad.